English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-10-29 14:20:51 · 12 answers · asked by Anonymous in Science & Mathematics Mathematics

12 answers

3(2x-9)-6=15
3(2x-9)=21
2x-9=7
2x=16
x=8

2006-10-29 14:26:02 · answer #1 · answered by Alex P 2 · 1 0

x=8

3(2x-9) - 6 = 15
add the six
3(2x-9) = 21
divide by the three
2x - 9 = 7
add the nine
2x = 16
divide by the two
x = 8

2006-10-29 14:31:10 · answer #2 · answered by Kat 2 · 1 0

x = 5 because it's three times 2x-9 then -6 ... equaling 15. so... whatever it is it has to take 15 away equaling 15. 3 x 2 x 5 =30 is the first part then minus 9 then minus 6 totaling 15 subtracted leaving 15 thereby having to total thirty to come out properly.

2006-10-29 14:38:09 · answer #3 · answered by Boliver Bumgut 4 · 0 1

8

2006-10-29 14:23:42 · answer #4 · answered by zo 3 · 1 1

there is no longer a answer, because it rather is merely an expression no longer an equation(no longer something to show what the priority equals) So i'm uncertain what the priority is looing for interior the respond so... First i'm going to boost the expression 4x+4[4(2x-9)+6]-15 4x+4[8x-36=6]-15 or 4x+sixteen(2x-9)+24-15 4x+32x-one hundred forty four+24-15 36x-a hundred thirty five Then component it 36x-a hundred thirty five 9(4x-15)

2016-12-28 07:58:06 · answer #5 · answered by Anonymous · 0 0

3(2x-9)-6=15
multiplying 6x-27-6=15
adding 6x-33=15
equating 6x=15+33(as there is = sign "-"changes to "+")
adding 6x=48
finding the value of x x=48/6
So, x=8

2006-10-29 14:44:46 · answer #6 · answered by dimplesoft 3 · 0 0

3(2x-9)-6=15

distribute the 3:
6x-27-6=15

add 6 to both sides:
6x-27=21

add 27 to both sides:
6x/6 = 48/6

Divide and get x by itself:
x=8

hope that helped

2006-10-29 14:34:42 · answer #7 · answered by Anonymous · 1 0

3(2x - 9) - 6 = 15
3(2x - 9) = 21
2x - 9 = 7
2x = 16
x = 8

2006-10-29 14:41:44 · answer #8 · answered by Sherman81 6 · 1 0

3(2x-9) -6 -(-6) = 15 - (-6) (inverse law for addition)
3(2x-9) = 21
6x - 27 = 21 ( distributive law)
6x - 27 -(-27) = 21 - (-27) (inverse law for addition)
6x = 48
(1/6)(6x) = (1/6)(48) (inverse law for multiplication)
1 x = 8
x = 8 ( identity property for 1 )

2006-10-29 14:36:17 · answer #9 · answered by sumone^^ 3 · 1 0

3(2x - 9) - 6 = 15

distribute the 3
6x - 27 - 6 = 15

combine like terms (-27 - 6)
6x - 33 = 15

get x by itself by subtracting 33 from each side
6x = 18

get x by itself by dividing by 6
x = 3

2006-10-29 14:28:22 · answer #10 · answered by Anonymous · 0 2

fedest.com, questions and answers